Endoscopic Assessment of Children with Esophageal Atresia: Lack of Relationship of Esophagitis and Esophageal Metaplasia to Symptomatology - Julie Castilloux; Dorothée Bouron-Dal Soglio; Christophe Faure (Canadian Journal of Gastroenterology)
BACKGROUND: Late complications of esophageal atresia (EA), particularly esophagitis and Barrett’s esophagus, are increasingly being recognized. With the exception of patients with dysphagia associated with esophageal stricture, it is unknown whether patient symptomatology can predict endoscopic findings.